Cost-effectiveness analysis of fosaprepitant versus aprepitant-based antiemetic regimens in children receiving highly emetogenic chemotherapy: individual patient-level analysis of a randomised trial - Rahul Kumar; Manraj Singh Sra; Azgar Abdul Rasheed; Archana Sasi; Deepam Pushpam; Atul Batra; Shuvadeep Ganguly; Sameer Bakhshi (BMJ Supportive & Palliative Care, 2026)
Objectives To assess the trial-based cost-effectiveness of an intravenous fosaprepitant-based antiemetic regimen compared with oral aprepitant, in combination with ondansetron and dexamethasone, among children receiving highly emetogenic chemotherapy in India and the USA using individual patient-level data. Methods Costs were estimated from a private payer perspective in India and the USA. Health outcomes were expressed as quality-adjusted life-years (QALYs). Incremental cost-utility ratio (ICUR) and incremental net monetary benefit (iNMB) were calculated. Uncertainty was evaluated through one-way deterministic sensitivity analyses. Results A total of 140 and 139 children were enrolled in the fosaprepitant and aprepitant groups, respectively. Mean QALYs were marginally higher in the aprepitant group (0.0118 vs 0.0116; difference: 0.0002). In India, mean costs were $33.94 in the fosaprepitant arm vs $19.73 in the aprepitant arm (difference: $14.21). In the USA, mean costs were $615.92 vs $809.73, respectively, in the two arms (difference: $193.81), favouring fosaprepitant. iNMB values of fosaprepitant compared with aprepitant were –$15.59 in India and $173.81 in the USA, indicating lack of cost-effectiveness for fosaprepitant in India but cost-effectiveness in the USA. In sensitivity analyses, the ICUR was most sensitive to the cost of fosaprepitant in India and to the utility value of the complete protection health state in the USA. Conclusions Intravenous fosaprepitant, administered in combination with ondansetron and dexamethasone, was not cost-effective compared with oral aprepitant-based combination therapy in India but demonstrated cost-effectiveness in the USA.